1994
DOI: 10.1037/0033-2909.116.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Consensus in interpersonal perception: Acquaintance and the big five.

Abstract: Consensus refers to the extent to which judges agree in their ratings of a common target. Consensus has been an important area of research in social and personality psychology. In this article, generalizability theory is used to develop a percentage of total variance measure of consensus. This measure is used to review the level of consensus across 32 studies by considering the role of acquaintance level and trait dimension. The review indicates that consensus correlations ranged from zero to about .3, with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
201
2
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(239 citation statements)
references
References 58 publications
32
201
2
4
Order By: Relevance
“…Good reliability was found, with all Cronbach's α > .80, apart from warmth, at .74, which is still considered acceptable inter-rater agreement. The high reliability fits with previous studies showing consensus at zero acquaintance (Albright, et al, 1988;Engell, et al, 2007;Kenny, Albright, Malloy, & Kashy, 1994) and shows that some physical features of the stimuli, visible to observers, drive trait impressions. High agreement was not due to recognition of sex of target driving the trait judgment, as agreement was high also within each sex (see Table 1).…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Good reliability was found, with all Cronbach's α > .80, apart from warmth, at .74, which is still considered acceptable inter-rater agreement. The high reliability fits with previous studies showing consensus at zero acquaintance (Albright, et al, 1988;Engell, et al, 2007;Kenny, Albright, Malloy, & Kashy, 1994) and shows that some physical features of the stimuli, visible to observers, drive trait impressions. High agreement was not due to recognition of sex of target driving the trait judgment, as agreement was high also within each sex (see Table 1).…”
Section: Methodssupporting
confidence: 88%
“…In Study 1, we showed that point-light walker stimuli depicting single gait cycles were reliably rated on six personality traits. This finding adds to a range of studies showing consensus at zero acquaintance (Albright, et al, 1988;Albright, et al, 1997;Ambady & Rosenthal, 1993;Engell, et al, 2007;Heberlein, et al, 2004;Kenny, et al, 1994).…”
Section: Discussionsupporting
confidence: 67%
“…These findings are consistent with a large literature showing substantial self-other agreement and rater consensus in judgments of key personality traits such as extraversion (Funder, 1980;Funder & Colvin, 1997;Human & Biesanz, 2011;Kenny, Albright, Malloy, & Kashy, 1994).…”
Section: Do People Notice Others' Self-esteem?supporting
confidence: 81%
“…Het is gemakkelijker om iemand accuraat en consistent te beoordelen op een persoonlijkheidsfactor wanneer de gedragingen die samenhangen met de factor duidelijk zichtbaar en in meerdere settings relevant zijn, dan wanneer ze minder zichtbaar of alleen in specifieke settings relevant zijn. Verschillende beoordelaars zijn het over het algemeen meer eens over duidelijk zichtbare aspecten van persoonlijkheid zoals Extraversie en Zorgvuldigheid, dan over meer intrapsychische factoren zoals Emotionele stabiliteit (Borkenau & Liebler, 1992;Funder & Dobroth, 1993;John & Robins, 1993;Kenny, Albright, Malloy & Kashy, 1994;Malloy e.a., 1997).…”
Section: Inleidingunclassified